Differentially expressed lncRNAs and miRNAs with associated ceRNA networks in aged mice with postoperative cognitive dysfunction - Wei, Changwei (Oncotarget, 2017)
Postoperative cognitive dysfunction (POCD) is a common postoperative complication observed in elderly patients. Using microarray analyses, we comprehensively compared long non-coding RNA (lncRNA), messenger RNA (mRNA), and microRNA (miRNA) expression profiles in hippocampal tissues from a mouse model of POCD and control mice. A total of 175 lncRNAs, 117 mRNAs, and 26 miRNAs were differentially expressed between POCD and control mice. Gene ontology (GO) and KEGG pathway enrichment analyses were performed to explore the principal functions of dysregulated genes. Correlated coding-noncoding co-expression (CNC) and competing endogenous RNA (ceRNA) expression networks were constructed using bioinformatics methods. lncRNA NONMMUT000708 correlated positively with expression of the inflammation-related gene Hif3a. lncRNAs NONMMUT043249 and NONMMUT028705 mediated gene expression by binding the transcription factor cAMP response element-binding protein (CREB). The constructed ceRNA network suggested lncRNA NONMMUT055714 binds competitively with miR-7684-5p, increasing expression of its target gene, Sorl1. Finally, eight dysregulated lncRNAs, four miRNAs, and ten mRNAs were confirmed via quantitative real-time polymerase chain reaction (PCR) in 10 POCD-healthy mouse paired samples. These results suggest that lncRNAs and miRNAs are involved in POCD pathogenesis and progression. Our ceRNA network will improve understanding of lncRNA-mediated ceRNA regulatory mechanisms operating during the pathogenesis of POCD.